The Puppet Thimplong: Assessment Form Performance and Values of Local Wisdom for Nganjuk Citizen - Dyah Indriyani, Putri; Triyanto, Triyanto; Malarsih, Malarsih (Universitas Negeri Semarang, 2019)
Thimplong puppet is an art from Nganjuk District, Pace especially. This puppet is a type of wood puppet with a story was raised the Panji stories. The purpose of this study is to analyze forms of performance and load values ​​of local wisdom in the art of Wayang Thimplong. The method used is a qualitative approach. Data collection techniques by using observation, interview and documentation. While the data analysis techniques with data triangulation technique. In addition, there are also technical validity of the data comprising data reduction, data presentation, and data verification / conclusion. The results showed that the shape of the show on the Wayang Thimplong contained the following elements: a story or player was played, shape or form of puppets, the music, the venue, the sound, and the audience in the performing arts Wayang Thimplong. In addition, the load Thimplong Puppet show the great value that local content is a religious value, the value of compliance, educational value, as well as ethical values ​​therein. Implications of this art can be used as teaching materials are local so it can be as a trigger to the public appreciation especially Wayang puppet Thimplong.